Racism as metaframe - Costa, Eliane Silvia (Revista do Instituto de Estudos Brasileiros, 2015)
This article discusses issues related to racism and is based mainly upon contributions of social psychology. Therefore, it mentions two concepts. They are: frame and metaframe. The first was theorized by social psychologist José Bleger and the second is an extension of that and it was written by René Kaës, theoretical psychoanalysis of social ties. The article concludes with situations involving social–cultural, historical and educational processes that reveal possibilities to address racism.